Uncovering diversity and abundance patterns of CO2-fixing microorganisms in peatlands - Le Geay, Marie; Mayers, Kyle; Sytiuk, Anna; Dorrepaal, Ellen; Küttim, Martin; Lamentowicz, Mariusz; Tuittila, Eeva-Stiina; Lauga, Béatrice; Jassey, Vincent E. J. (Npj Biodiversity, 2025)
Microorganisms play a crucial role in the carbon (C) dynamics of peatlands — a major terrestrial C reservoir. Because of their role in C emissions, heterotrophic microorganisms have attracted much attention over the past decades. CO 2 -fixing microorganisms (CFMs) remained largely overlooked, while they could attenuate C emissions. Here, we use metabarcoding and digital droplet PCR to survey microorganisms that potentially fix CO 2 in different peatlands. We demonstrate that CFMs are abundant and diverse in peatlands, with on average 1021 CFMs contributing up to 40% of the total bacterial abundance. Using a joint-species distribution model, we identified a core and a specific CFM microbiome, the latter being influenced by temperature and nutrients. Our findings highlight that ASV richness and community structure were direct drivers of CFM abundance, while environmental parameters were indirect drivers. These results provide the basis for a better understanding of the role of CFMs in peatland C cycle inputs.